Niche overlap of mountain hare subspecies and the vulnerability of their ranges to invasion by the European hare; the (bad) luck of the Irish - Caravaggi, Anthony; Leach, Katie; Santilli, Francesco; Rintala, Jukka; Helle, Pekka; Tiainen, Juha; Bisi, Francesco; Martinoli, Adriano; Montgomery, W. Ian; Reid, Neil (Biological Invasions, 2016)
Niche conservatism is the tendency of related species to retain ancestral tolerances after geographic separation. We used Ecological Niche Modelling and Principal Components Analysis of bioclimatic and habitat variables to describe the extent of the species niche, and degrees of bioclimatic–habitat niche conservatism within the mountain hare (L. timidus) clade. Mountain hare niche space was contrasted with that of the European hare (L. europaeus), to shed light on species interactions in contact zones throughout Europe. All five subspecies of mountain hare had quantifiably distinct niches. Fennoscandian (L.t. sylvaticus, L.t. timidus) and highland (L.t. scoticus, L.t. varronis) subspecies, however, were most similar, exhibiting greatest apparent niche conservatism. They inhabit tundra, boreal forest and uplands, and, hence are presumed most similar to the ancestral form. The Irish hare was distinct, being consistently distinguished from other mountain hares in both 2D and nth dimensional (4D) niche space. The ecological distinctiveness of the Irish hare provides further evidence that it is an Evolutionarily Significant Unit, particularly vulnerable to displacement by introduced European hares with which it competes and hybridises. Projections under global climate change suggest that, by 2070, bioclimatic space for invasive European hares in Ireland will expand (by 79%) but contract for endemic Irish hares (by 75%), further facilitating their replacement. The near complete species replacement of the heath hare (L.t. sylvaticus) in southern Sweden, where the European hare has also been introduced, may suggest a similar fate may be in store for the Irish hare.